Influence of Gypsum on the Residual Properties of Fly Ash-Slag-Based Alkali-Activated Concrete - Sandeep G. S.; Poornachandra Pandit; Shreelaxmi Prashanth; Jagadisha H. M. (Civil Engineering Journal, 2024)
High-temperature exposures of concrete lead to serious damage in concrete structures, resulting in the significant decay of mechanical properties and spalling of concrete. Alkali-activated concretes (AAC) of blended aluminosilicate precursors and activators have been proven to have higher thermal endurance than conventional portland cement concrete. Incorporation of gypsum (GY) in alkali-activated systems has proven to positively impact the mechanical properties when adopted in controlled amounts. GY releases SO42- to the binder system, which helps in the formation of ettringites, along with Ca2+, which leads to the formation of hydrates. This causes a reduction in porosity and improves strength gain. Incorporation of GY into the fly ash-slag-based alkali-activated system further improves thermal endurance by retaining considerable residual strengths even after 800°C exposure. In the present study, the influence of GY on the residual mechanical properties of fly ash-slag-based AAC is investigated to explore the thermal endurance of the ternary mix at elevated temperatures. The mechanical properties of fly ash (FA), Ground Granulated Blast Furnace Slag (GGBS), and gypsum (GY) ternary blended AAC subjected to elevated temperatures are studied in comparison with conventional portland cement concrete (control mix). AAC design mixes with varying proportions of GY as a replacement to FA-GGBS precursor are tested for mechanical properties to obtain the optimum mix. The residual mechanical properties of the FA-GGBS-GY optimum ternary AAC mix are obtained after exposure to elevated temperatures up to 800°C. The morphology and microstructural characteristics of AAC are studied by Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray Spectroscopy (EDS) analyses to investigate the influence of gypsum on the thermal endurance of concrete when exposed to elevated temperatures. Improved thermal endurance is observed for AAC when FA-GGBS precursors are replaced with 5% of GY as compared to the thermal endurance of conventional portland cement concrete (PCC) of the same compressive strength. Doi: 10.28991/CEJ-2024-010-03-017 Full Text: PDF